Federal-local partnerships on immigration law enforcement: are the policies effective in reducing violent victimization? - Baumer, Eric P. (Criminology & public policy, 2023)
Research Summary Our understanding of how immigration enforcement impacts crime has been informed exclusively by data from police crime statistics. This study complements existing research by using longitudinal multilevel data from the National Crime Victimization Survey for 2005-2014 to simultaneously assess the impact of the three predominant immigration policies that have been implemented in local communities. The results indicate that the activation of Secure Communities and 287(g) task force agreements significantly increased violent victimization risk among Latinos, whereas they showed no evident impact on victimization risk among non-Latino Whites and Blacks. The activation of 287(g) jail enforcement agreements and anti-detainer policies had no significant impact on violent victimization risk during the period. Policy Implications Contrary to their stated purpose of enhancing public safety, our results show that the Secure Communities program and 287(g) task force agreements did not reduce crime, but instead eroded security in U.S. communities by increasing the likelihood that Latinos experienced violent victimization. These results support the Federal government's ending of 287(g) task force agreements and its more recent move to end the Secure Communities program. Additionally, the results of our study add to the evidence challenging claims that anti-detainer policies pose a threat to violence risk.